ACUTE BEHAVIOR OF HEART RATE, BLOOD PRESSURE AND RATE PRESSURE PRODUCT IN ADULT WOMEN DURING A GYMNASTICS SESSION (Fiep Bulletin - online, 2015)
The physical inactivity directly is related to a bigger cardiovascular risk and this social behavior is present in the entire world. The exercise must promote change in health behavior to include the activity physical as habitual. Objective: This study investigated which HEART RATE (HR), BLOOD PRESSURE (BP) and RATE PRESSURE PRODUCT (RPP) acute physiological answers resultant of the practical of gymnastics session with predominance force training and in gymnastics session with predominance of the muscular resistance located training (RML) in order to identify the possibility to have a bigger overload imposed to the myocardium. Methodology: The study  was descriptive 3of transversal analysis and the sample was composed for 8 individuals and an element reference all of the feminine sort. The blood pressure was measured by a digital sphygmomanometer CITZEN® . Resulted: It verified the collected group did not present significant difference of the HEART RATE, BLOOD PRESSURE and RATE PRESSURE PRODUCT in sessions with predominance of force training and in session with predominance RML. Already the element reference presented values variable below of the values found in the group in both the analyzed sessions. Conclusions: The analyzed group inside of a perspective intra-group did not present significant difference (P< 0,05) enters the averages of the RML sessions and force. When comparing the element reference was observed that in the majority of the averages it met outside of the averages in the two types of session. Key-words: located gymnastics, blood pressure, heart rate, rate pressure product.
Keywords: .